2011
DOI: 10.1007/s11947-011-0642-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Legume Flours on Quality and In Vitro Digestibility of Starch and Protein from Gluten-Free Cakes

Abstract: The aim of the study was to investigate the impact of incorporation of different legumes (chickpea, pea, lentil and bean) on quality, chemical composition and in vitro protein and starch digestibility of gluten-free layer cake (rice flour: legume flour, 50:50). The incorporation of legume flours increased the batter viscosity and, with exception of chickpea, resulted in higher specific cake volume than that in control. Chickpea and pea containing cakes had the brightest and the most yellowish crust. The legume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
119
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 32 publications
21
119
0
10
Order By: Relevance
“…Gularte et al (2011) have also developed gluten-free cakes when rice flour was substituted with the flour of several legumes, obtaining a SV of 2.9 mL/g -1 for the cake with 50% of beans flour, being this value close to that of CM60 in the present study.…”
Section: Physical Characteristicssupporting
confidence: 77%
“…Gularte et al (2011) have also developed gluten-free cakes when rice flour was substituted with the flour of several legumes, obtaining a SV of 2.9 mL/g -1 for the cake with 50% of beans flour, being this value close to that of CM60 in the present study.…”
Section: Physical Characteristicssupporting
confidence: 77%
“…Gomes et al, (2015) reported that all the extruded bean flour added cakes had an acceptability score of above six. The property of legumes to promote greater hardness of cakes was also reported by Gularte et al, (2011) who found a significant increase in hardness of cakes prepared with beans, chickpeas and peas.…”
Section: Effect Of Independent Variables On Oaa Scoresupporting
confidence: 60%
“…A single-bowl mixing procedure was used for making gluten-free layer cakes according to Gularte et al [14]. The basic recipe gluten free layer cake and flaxseed flour replaced formulations up to 60% rice flour are shown in Table 1.…”
Section: Gluten-free Layer Cake Preparationmentioning
confidence: 99%